Study on the dynamic characteristics of bit anchor cable drilling in the gravel sediments of a soft rock bottom hole - Gao, Kuidong (Strojniški vestnik, 2023)
During the pore-forming stage of floor heave treatment, the phenomenon of gravel sediment accumulation in the bottom hole often occurs, which causes great difficulties in the normal installation of the anchor cable. Based on this observation, a new anchor cable installation method was proposed, which involves installing a drill bit at the front end of the anchor cable to assist its drilling. With the help of an anchor cable drilling test bench, the influence of the bit, motion parameters, and hole environment on the performance of anchor cable drilling was studied. Through the co-simulation of the discrete element method (i.e., multibody dynamics (DEM-MBD)), the drilling process of the bit anchor cable was simulated, and the dynamic characteristics of the bit anchor cable drilling in the bottom hole gravel sediment were analysed. The results show that installing a drill bit in front of the anchor cable can greatly reduce the drilling resistance and hamper torque during anchor cable drilling. When the rotational direction of the bit anchor cable is consistent with the spiral direction of the anchor cable, the bit anchor cable can exhibit better drilling performance. The drilling resistance and hindering torque of the bit anchor cable are the largest when drilling in soaked particles, followed by drilling in dry particles, and the smallest occurs when drilling in moist particles. The research results can provide reference for the parameter setting of anchor cable auxiliary installation equipment.
Keywords: anchor cable; bit; dinamične lastnosti; diskretna zrna; dynamic characteristic; gravel drilling; sidrne vrvi; vrtalni nastavki; vrtanje v pesek